The VaRP Project: qualitative evaluation of the training effectiveness of Post Graduate Specializations for health professionals - Cosentino, Chiara (Acta Biomed, 2020)
INTRODUCTION: The healthcare professionals’ specialized training has a positive impact on professional values, patient’s outcome, and promotion of evidence-based practices. To raise the educational standard, the University of Parma has created Post Graduate Specializations which, in addition to learning sector-specific techniques and skills, include the acquisition of soft skills. Aim of the study is investigating the perception of the tutors dedicated to the organization, management, and teaching of the Post Graduate Specializations on the skills gained and the changes achieved in clinical practice, training, and research. MATERIALS AND METHODS: Qualitative research was carried out through a semi-structured interview to 11 tutors who have been coordinating the Post Graduate Specializations. RESULTS: The Qualitative analysis developed “thick” descriptions characterized by analytical density and interpretative richness. The emerging thematic nuclei were: General/unpredicted aspects, Professional empowerment, Satisfaction, Professional outcomes, Limits of the Post Graduate Specializations, and Development areas. CONCLUSIONS: We identified the most effective areas of the Post Graduate Specializations that emerged consistently from the interviews. We hypothesized that the values and mission the Scientific Board, are effectively lived and championed in the everyday activities of the Post Graduate Specializations. Some domains still need to be furtherly developed, as the professional record, the absence of a “follow up” relationship with former students, and the effective management of workload both for students and tutors. The rise of these limits, can be particularly fruitful, as it gives the chance to identify the development trajectory the post-graduate trainings should pursue to raise the standard of excellence. (www.actabiomedica.it)